Ikatan Mahasiswa Muhammadiyah (IMM) dan Peranannya dalam Mewarnai Tradisi Intelektual Mahasiswa di Kota Medan - Harahap, A. Fachriza Haqi; Monang, Sori; Muchsin, Kasron (Warisan: Journal of History and Cultural Heritage, 2021)
This article discusses the history and role of the Muhammadiyah Student Association (IMM) in coloring the intellectual life of students in Medan City. This study uses historical research methods with five stages, namely topic selection, source collection, source criticism, interpretation, and historiography, with a social approach. In this article, the focus of the problem that the author wants to examine is related to the history and role of IMM in Medan City. The result of this study is that the author succeeded in explaining the history and presence of IMM in Medan City. In addition, the author also succeeded in finding that IMM Medan City played a role in coloring the intellectual traditions of students in Medan City, especially Islamic students. IMM Medan City continues to be a forum for Muhammadiyah cadres to form intellectuals. IMM Medan City also continues to striveÂ